Japanese Buddhism - Eliot, Charles (E. Arnold & Co., 1935)
Buddhism is a religion that offers a spiritual path for transcending the suffering of existence. Samsara, the endless cycle of birth, death and rebirth to which all beings are subject, results from the consequences incurred by oneʼs karma, the sum of good and bad actions that accumulates over many lives. Release from this endless cycle is achieved only by attaining enlightenment, the goal for which Buddhists strive. A buddha (“enlightened one”) is an all-knowing being who has reached that perfect state of transcendent knowledge in which the fires of greed, hate, and delusion are quenched and, upon passing into nirvana (“blowing out, to become extinguished”), is never subject to rebirth again.